Regional economic communities influencing policy: a study of information communications technology policy (on telecommunication) of four SADC countries - Maulana, Godfree W. (My University, 2017)
In the last three decades’ information and communication technology (ICT) has been a catalyst for an unprecedented social and economic revolution. In part, the revolution can be accredited to the rapid change in technology over the years, while on the other hand it can be attributed to reform changes which include, but are not limited to, the liberalisation of the sector. Countries introduced reforms in the ICT sector via targeted policy changes which facilitated change in the sector. They either formulated policies with the objective to remedy specific issues in their environment or adopted policies guided by the regional bodies. This study evaluates the extent to which country specific ICT policies adopt recommendations made by regional bodies. The Southern African Development Community (SADC) region is used for this research with four Member States ICT policies evaluated for conformity to the SADC recommendations, specifically with respect to the SADC Protocol on Transport, Communication and Meteorology. The policies are also evaluated against policy formulating techniques recommended when formulating policies. The focus of this study is the telecommunications policies of each of the chosen Member States and policy recommendations by SADC on same. The study employed desktop research and an analysis of the relevant documentation, which were interrogated for specific content with respect to previously identified policy objectives. These were then analysed against the SADC Protocol and the policy techniques. The policy formulating techniques are to ensure the policies under analysis are not conforming to the SADC recommendation due to poor policy writing techniques, however it is imperative for the reader to note that the research is on the conformity of the Member States to the policy recommendations by SADC. It emerged from the research that the Member States in SADC, under study, adopted policy recommendations made by SADC to varying degrees. There is also evidence of the use of specific policy-formulation techniques. Countries that have some evidence of use of policy techniques have better policy as evidence by achievements of the policy objectives. In order to formulate good policy not only must the regional body provide concise policy recommendations, the Member States must be able to formulate policy that would be in line with the recommendations. Regional bodies have an influence in member state policy formulation and there are benefits to be gained by regional economic communities if they have harmonised polices supported by Mwasha (nd). It also emerged that whilst there is policy reform in the ICT sector there is a dearth of research with regards to policy analysis and evaluation of the existing policies.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Arts (ICT Policy and Regulation), 2017
Keywords: Southern African Development Community; Telecommunication policy; Information technology--Government policy; Telecommunication